Exploring performance of athletic individuals: Tying athletic behaviors and big-five personality traits with sports performance - Li, Q.; Xiao, D.; Zeng, Q. (PLOS ONE, 2024)
The paper aims to investigate the interplay of sports athletic behavior between big-five personality traits and sports performance in China. The study acquired cross-sectional responses on the questionnaire from 260 Chinese sports athletes, including males and females. Fuzzy analysis techniques were applied to examine the results of the study. Fuzzy TODIM assessment, and fuzzy decision analysis technique applied to draw inferences. The results established that big-five personality traits are significant predictors of athletic behaviors; however, neuroticism is found to be insignificant. The interplay of athletic behavior of sports athletes is also significant in sports game performance. The role of athletic behavior in the nexus between personality traits and sports performance is also significant. Gender also has a significant role in behavior and sports performance. Chinese educational institutional and sports administrations should strive to encourage psychological training programs are enhance mental resilience for effective performance. Valuing sports opportunities for females to shape gender equality would promote sports performance at the school and college levels. Therefore, policy makers need to take such initiatives for a physically academic grooming of the individuals.